Factors contributing to prosthodontic exam anxiety in undergraduate dental students - Alammari, Manal R (Adv Med Educ Pract, 2019)
INTRODUCTION: Prosthodontics is a challenging subject for dental students. This study explores the incidence of exam anxiety among prosthodontics students and the variables that moderate it. METHODS: A cross-sectional, self-administered questionnaire was distributed to fourth-year undergraduate students immediately before examinations, with a 77% response rate (55.7% female, 44.3% male). RESULTS: A lack of time to prepare before exams and an inability to recall before exams were the main factors affected by gender. In addition, 63.5% of male students agreed that social media and mobile phones are distractions, while 81.8% of female students disagreed (P<0.001). Within the removable prosthodontic courses (preclinical or clinical), 61.0% of students agreed that a lack of time to prepare before exams is an issue with the clinical course, while 58.5% of the students moderately agreed it is an issue with the preclinical course (P=0.044). A lack of time to prepare, fear of failure, and the time of the examination were of greater concern with regard to quizzes than with mid-term examinations. CONCLUSION: This study highlights the presence of exam anxiety among prosthodontics students, as well as how that anxiety is influenced by gender, clinical courses, and the type of exam. This study suggests that students should be taught strategies to improve their study, life and time-management skills in order to overcome exam anxiety. This study additionally suggests that improving success rates in dental school requires placing an increased focus in the curriculum on test competency and examination patterns.